Cytogenetic study on Thai brow-antlered deer, Cervus eldi siamensis and Thamin brow-antlered deer, Cervus eldi thamin (Artiodactyla, Cervidae) by conventional staining method - Monthira Monthatong1 (Songklanakarin Journal of Science and Technology (SJST), 2008)
Cytogenetics of Thai brow-antlered deer (Cervus eldi siamensis) were studied in comparison with those of Thamin brow-antlered deer (Cervus eldi thamin). Blood samples were taken from the two subspecies kept in Khoa Kheow Open Zoo, Chonburi Province. After the standard whole blood lymphocyte were cultured in presence of colchicine, the metaphase spreads were performed on microscopic slides and air-dried. Conventional Giemsa’s staining were applied to stain chromosome. Thai and Thamin brow-antlered deers exhibited the same karyotype with diploid number of 2n = 58 (NF = 70) for females and 2n = 58 (NF = 71) for males. The types of autosome are 6 large metacentric, 6 large submetacentric, 8 large telocentric, 20 medium telocentric and 16 small telocentric chromosomes. In addition, satellites are clearly observed in terminal position on the short arm of a pair of chromosome 7. The X chromosome is the largest telocentric and the Y chromosome is the smallest metacentric chromosome. The karyotype formula of Thai and Thamin brow-antlered deer is as follows: 2n (58) = Lm6+Lsm6+Lt8+Mt20+St16+sex chromosome